(untitled) (Research, Society and Development, 2023)
Objective: The objective of the study is to describe different guidelines on dental care in pregnant women. Methodology: An exhaustive search of the literature was carried out in the "PUBMED", "Science Direct" and "Scopus" databases using the keywords: through the keywords "Pregnant Woman", "Pregnacy" and "Dental Care" with the boolean AND connector, where a total of 21 scientific articles were obtained according to the inclusion and exclusion criteria. Results: There are several considerations that must be taken into account when caring for a pregnant patient where care should be taken. Be careful with the type of drugs used, use of ionizing radiation, among others. Conclusion: Pregnancy leads to a set of physiological changes where there is a greater susceptibility to the development of oral morbidities such as caries and periodontal disease. The teaching of adequate hygiene as a whole with periodic dental check-ups for pregnant women are key factors in avoiding serious pathological conditions.